PENGELOLAAN ASET DAERAH DI DEWAN PERWAKILAN RAKYAT DAERAH INDRAGIRI HILIR PERIODE 2009-2014 - R. Enny Irawanti; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
R. Enny Irawanti, 1301156939 management of regional assets in the representative of representative country of indragiri region period 2009-2014. Supervisor Dra. Hj. Wan Asrida, M.Si In the current era of regional autonomy, there is a heavy burden on the local government and the House of Representatives, the burden is an effort to accelerate the growth and regional development, prosperity, absorb and run the expectations of the community. DPRD is an element of local government as a vehicle to implement democracy based on Pancasila. So in carrying out its duties and functions, the DPRD holds to the principles of regional autonomy within the framework of the Unitary State of the Republic of Indonesia. Based on the results of the BPK-RI audit of the Local Government Financial Statements, various issues concerning the fixed asset account which are commonly among them are fixed asset values presented in the balance sheet not yet supported by adequate records, fixed assets unknown, fixed assets held by other parties, fixed assets are not returned by former members of parliament. The purpose of this study is to describe the management of local assets and obstacles in Indragiri Hilir Regency DPRD Period 2009-2014. This research is a qualitative research. This research was conducted in Indragiri Hilir Regency DPRD Period 2009-2014. Techniques used to collect data in this study are (1) Interviews, (2) Library Studies, and (3) Documentation. The conclusions of this study indicate that 1) the management of regional assets in Indragiri Hilir Regency DPRD Period 2009-2014 has not been maximized. 2) Lack of DPRD members who really understand the process of asset management. 3) Limited capacity of DPRD members in the management of income, finance and regional assets. 4) The incomplete system and procedures of financial management and regional assets in Indragiri Hilir Regency DPRD. 5) There is still a lack of experts in the Indragiri Hilir Regional House of Representatives who is professional, namely in the management of regional assets (Regional Property).Keyword: management, assets